THE NEUROAESTHETICS OF FASHION DESIGN - Fenton, Veronica (International Journal of Research -GRANTHAALAYAH, 2021)
Close your eyes and imagine that you are in an art museum. You look over your right shoulder and see a painting of a lush garden landscape. Try to investi- gate it further. Observe the abundance of pastel-colored flowers, engaging van- tage points and mystical partially hidden pathways.a Then, consider how the landscape makes you feel. Now, keep your eyes closed and imagine another scenario. You are sitting in the front row of Christian Dior’s “The Garden of Earthly Delights” fashion show.b Try to concentrate on the clothing. Observe the plethora of delicate, soft-hued, floral-print gowns. Finally, consider how the fashions make you feel.